Academic Careers in Global Pulmonary and Critical Care Medicine - Papali, Alfred; V Diaz, Janet; Carter, Jane; Ferreir, Juliana C; Fowler, Rob; Gebremariam, Tewodros H; Gordon, Stephen B; Lee, Burton W; Murthy, Srinivas; Riviello, Elisabeth D; West, Eoin; Adhikari, Neill Kj (Journal of Global Health, 2020)
The burden of respiratory and critical illness is high worldwide, yet specialist care is underrepresented in low- and middle-income countries (LMICs) [1]. For many areas of medicine, the past decade has witnessed tremendous growth in global health opportunities for trainees; however, these opportunities tend to be restricted to individual institutions and geographic regions and academic global pulmonary and critical care medicine (PCCM) remains a relatively novel concept [2]. Consequently, PCCM fellows and junior faculty at institutions with limited global health mentorship have little guidance in building successful global health careers.
Viewpoints
Keywords: Respiratory illness; Global health; Private practice; Traditional academic medicine